First report from the select Committee on nationalised industries : ministerial control of the nationalised industries, volume 1, report and proceedings of the Committee session 1967-68 - United Kingdom (London : H.M.S.O., 1968)
The Select Committee appointed to examine the Reports and Accounts of the Nationalised Industries established by Statute whose controlling Boards are appointed by Ministers of the Crown and whose annual receipts are not wholly or mainly derived from moneys provided by Parliament or advanced from the Exchequer ; and of the Independent Television Authority, Cable and Wireless Ltd., and the Horserace Totalisator Board. The report is divided into four parts. Part I, deals with the various functions which the Bank performs. Part II, discusses the organization of the Bank in terms of the staff, departments, investments and the Bank's own finances. Part III discusses the application to the Bank of some of the principles set out in the Report of the Nationalised Industries Committee of 1967-68 on Ministerial Control of the Nationalised Industries (H.C. 371 (1967-68)) and also covers the financial relationship between the Bank and the Government. Part IV considers the question of the proper degree of accountability to which the Bank should be subjected.
rpm 08/05/2018
Ref
Keywords: Nationalization; Nationalised industries